2020
DOI: 10.1080/14786419.2020.1756803
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of 2,5-diketopiperazines from Lysobacter capsici AZ78 with activity against Rhodococcus fascians

Abstract: Inhibitory activity of the biocontrol bacterial strain Lysobacter capsici AZ78 is related to the production of cyclo(L-Pro-L-Tyr), a 2,5-diketopiperazine with in vitro and in vivo toxic activity against Phytophthora infestans and Plasmopara viticola. Further investigation of culture filtrate organic extracts showed its ability to produce other 2,5-diketopiperazines. They were isolated and identified by spectroscopic ( 1 H NMR and ESIMS) and physic (specific optical rotation) methods as cyclo(L-Pro-L-Val), cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Li et al isolated two cyclic dipeptides, cyclo( d -Pro- l -Tyr), and cyclo( l -Pro- l -Tyr) from Lactobacillus reuteri and found that the latter exhibited antibacterial activity against Staphylococcus aureus [ 34 ]. Cimmino et al have isolated five DKPs, cyclo( l -Pro- l -Tyr), cyclo( l -Pro- l -Val), cyclo( d -Pro- d -Phe), cyclo( l -Pro- l -Leu), and cyclo( d -Pro- l -Tyr) with antibacterial activity against phytopathogenic Gram-positive bacterium Rhodococcus fascians LMG 3605 [ 35 ]. Cyclo( l -Pro- l -Phe), produced by Pseudonocardia endophytica , showed antibacterial activity against Gram-negative bacteria ( Xanthomonas campestris and Xanthomonas malvacearum ) and antifungal activity against ( Fusarium oxysporum and Fusarium solani ) [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Li et al isolated two cyclic dipeptides, cyclo( d -Pro- l -Tyr), and cyclo( l -Pro- l -Tyr) from Lactobacillus reuteri and found that the latter exhibited antibacterial activity against Staphylococcus aureus [ 34 ]. Cimmino et al have isolated five DKPs, cyclo( l -Pro- l -Tyr), cyclo( l -Pro- l -Val), cyclo( d -Pro- d -Phe), cyclo( l -Pro- l -Leu), and cyclo( d -Pro- l -Tyr) with antibacterial activity against phytopathogenic Gram-positive bacterium Rhodococcus fascians LMG 3605 [ 35 ]. Cyclo( l -Pro- l -Phe), produced by Pseudonocardia endophytica , showed antibacterial activity against Gram-negative bacteria ( Xanthomonas campestris and Xanthomonas malvacearum ) and antifungal activity against ( Fusarium oxysporum and Fusarium solani ) [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Strains of the genus Lysobacter are Gram-stain-negative, non-flagellated and flexing thin rods forming mucoid colonies [1]. Researchers are very interested in Lysobacter strains for their potential of producing mycolytic and bacteriolytic enzymes and antibiotic compounds [2–5]. Christensen and Cook first established the genus Lysobacter in 1978 [6] and, at the time of writing, this genus currently comprises 61 validly published and 12 invalidly published species (LSPN; www.bacterio.net) .…”
Section: Full-textmentioning
confidence: 99%
“…The latest studies on AZ78 metabolic profile strongly indicated that it is abundant in various antibiotic compound classes. Several bioactive 2,5-diketopiperazines have been identified and/or isolated from extracts of AZ78 cultures grown on nutrient-rich growth media [ 19 , 23 ]. Furthermore, genetic and analytical results have indicated the production of other bioactive compounds by AZ78 probably related to HSAF and WAP-8294A derivatives [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Extracts were evaluated for their antibacterial activity against Rhodococcus fascians LMG 3605 and anti-oomycete activity against P. ultimum using a resazurin-based microtitre assay. Antibacterial assays against R. fascians were performed as previously described by [ 23 ]. In brief, 140 µL of LB 1:10 were added to the wells of a sterile 96-well microtitre plate and amended with 20 µL of extract.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation